A seven-layered model architecture for Internet of Vehicles. Issue 1 (2nd January 2017) - Contreras-Castillo, Juan; Zeadally, Sherali; Guerrero Ibáñez, Juan Antonio
ABSTRACT: In the last decade, many vehicles which contain components to monitor different conditions (such as driver monitoring, tire pressure, oil pressure, vehicle speed, acceleration and position) have emerged. Internet of Things (IoT) is enabling the collection of different types of information from a given environment. The integration of results from both trends has led to the emergence of the concept of Internet of Vehicles (IoV). The implementation of IoV requires devices (sensors, personal devices, actuators, among others) to communicate with other devices and the infrastructure using different technologies. Such device interactions face several design challenges such as incompatibility among the devices, different qualities and response times for the Internet connection, limited processing and storage capabilities. To address these challenges, we propose a comprehensive framework that supports a layered design architecture capable of providing seamless integration for inter-device communication into the IoV ecosystem. We also present a review of recently proposed IoV architectures and discuss their salient differences with our proposed architecture.